Aromatization of Ethylene – Main Intermediate for MDA? - Vollmer, Ina; Abou‐Hamad, Edy; Gascon, Jorge; Kapteijn, Freek (ChemCatChem, 2020)
Methane dehydroaromatization (MDA) over Mo/HZSM‐5 has been hypothesized in literature to proceed via a two‐step mechanism: methane is first converted to ethylene on the molybdenum (Mo) functionality and then ethylene is oligomerized, cyclized and dehydrogenated on the Brønsted acid sites (BAS) of the HZSM‐5 support. This hypothesis is tested by studying the conversion of ethylene at the same conditions as used for MDA, namely 700 °C, atmospheric pressure, and by co‐feeding experiments with H2 and CH4. Our results suggest that ethylene is not the main intermediate for MDA, because the aromatic selectivities obtained from methane conversion are higher than selectivities measured during ethylene conversion. Furthermore, carbonaceous deposits formed during MDA have a lower density, are more hydrogenated and more active than the ones formed during ethylene aromatization (EDA). Similarly as for MDA, an activation period in which Mo carburizes to its active phase and an induction period, in which aromatics formation rates increase to their maximum are observed for ethylene conversion. The induction period, which was explained by the buildup of a hydrocarbon pool (HCP) is much faster with methane than with ethylene. This period, is attributed to a slow buildup of hydrocarbons, strongly adsorbed on Mo sites, because it is only observed with catalysts containing Mo. Hydrogen co‐feeding with ethylene leads to the formation of more reactive coke species and a significantly prolonged lifetime of the catalyst, but not to a faster buildup of the HCP. Does it all revolve around ethylene? According to our study this is very unlikely. In contrast to what had been hypothesized, the formation of aromatics from methane does not proceed solely via the formation of ethylene in a first step. Likely other intermediates and aromatics can directly form on Mo, while intermediate alkenes get aromatized on Brønsted acid sites in the zeolite pores of the catalyst.